Perceived influence of social media on nursing practice among nurses in a nigerian south westen tertiary health institution - Olufemi Oyebanji Oyediran; Jacob Adeyemi Adeniran; Matthew Idowu Olatubi; Oreofe Iyanuoluwa Ojo; Emmanuel Olufemi Ayandiran (Elsevier, 2024)
Social networking sites and the use of social media have got popularity among health professionals in recent times. This study assessed perceived influence of social media on nursing practice among clinical nurses working in a University Teaching Hospital in Nigeria.This study adopted a descriptive cross-sectional design, and stratified random sampling was adopted to select 205 respondents. Data were collected with the aid of a structured questionnaire and were analyzed with Statistical Package for Social Sciences (SPSS) version 25. Descriptive (frequency table, figures, mean and standard deviation) and inferential statistics (spearman rho Pearson correlation and Logistics regression) were used to present the data.Findings showed that the mean age of the respondents was 34.65 ± 8.49 years. Commonly used social media by the respondents were WhatsApp (94.6 %) and Facebook (92.7 %). A little above half (52.2 %) perceived social media benefits as high, 47.4 % perceived risks of social media to nursing practice as high and 63.9 % of the respondents spent at least 4 h on social media daily. Also, majority of the respondents identified knowledge about social media applications; accessibility to information; and availability of evidence-based information on social media. Single respondents were 8 times likely to use social media more than other marital status counterparts (P < 0.05, Odd ratio- 8.62, CI: 70.41 - 1.05), There was significant relationship between perceived benefits & disadvantage of social media and extent of usage {r = 0.740, df = 203p = 0.001}.This study concluded that nurses are using social media and majority of them are using WhatsApp and Facebook and they also believe that social media help to foster communication among nurses and other health care providers irrespective of the distance.